Consumer ethnocentrism in Malaysia towards Petronas petrol station: a case study of Klang Valley area / Mohamad Firdaus Mohamad Zaid - Mohamad Zaid, Mohamad Firdaus (2016)
Since recent years globalization has opened and exposed local and foreign marketers to greater market opportunity and from that consumers around the world are exposed to a broad number of domestic and foreign brand choices that are easily available to them(Teo, Mohamad, & Ramayah, 2011). So, from that this study is will focus on consumer ethnocentrism and its effect on perception towards local brands(Teo et al., 2011). In this study the based on the dimensions of the Consumer Ethnocentrism towards Petronas Petrol Station in Klang Valley Area it will be investigated. The impact and relationship of these dimensions of Consumer Ethnocentrism towards Petronas Petrol Station in Klang Valley Area will also be analysed. The location of this study will be at Klang Valley Area, Kuala Lumpur, Malaysia so the result will not be generalized. This research will be using frequency statistics, descriptive analysis, reliability analysis, regression analysis, Pearson’s correlation analysis and also One Way Anova analysis in answering the objective of the research. Recommendations also will be made based on the findings.